Análise da produção pesqueira artesanal na Região do Médio Madeira - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
The present study objective is to analyze the artisanal-fish species production landed in the Fisherman’s Colony Z-31 Dr. Renato Pereira Gonçalves, from 2018 to 2019, in the municipality of Humaitá, Amazonas, through methods of quantification and classification of fish stocks, aiming to stablish preliminary information about the exploitation status in order to orientate public policies of sustainable management in the region. In chapter one, a historic of how the fish monitoring occurred so far by analyzing the production from 2009 to 2012 provided by the Laboratório de Ictiologia e Pesca – Universidade Federal de Rondônia (LIP/UNIR), and using non-parametrical analysis techniques. In chapter two, a new method of fish monitoring applied to the local reality is presented, tested and validated. At last, in chapter three, the data generated in the chapter two is used to estimate the fish stock from the most explored fish population in the region.
Artisanal fishing production analysis of the Medium Madeira Basin
Keywords: Manejo sustentável; Humaitá (AM); Pesca multiespecífica; Refinamento da pesca; Dinâmica do desembarque pesqueiro; CIÊNCIAS AGRÁRIAS: RECURSOS PESQUEIROS E ENGENHARIA DE PESCA; Estoques Pesqueiros; Monitoramento Pesqueiro; Humaitá; Rio Madeira; Pesca Artesanal